Mastering the Raspberry Pi - Gay, Warren (Apress : Imprint: Apress, 2014)
You probably already know that the Raspberry Pi is an excellent teaching tool. If you want to teach Linux basics or Python programming or basic electronics, it's a great place to start. But what if you are an electronics engineer or a Linux systems administrator or a very experienced maker? You want to know all of the details and inner working of the Raspberry Pi -- how to (figuratively or maybe even literally) make it get up and dance without wading through basics and introductory material. If you want to get right into the pro-level guts of the Raspberry Pi, complete with schematics, detailed hardware explanations, messing around with runlevels, reporting voltages and temperatures, and recompiling the kernel, then Mastering the Raspberry Pi is just the book you need. Along with all of the thorough explanations of hardware and operating system, you'll also get a variety of project examples and explanations that you can tune for your own project ideas. You'll find yourself turning to Mastering the Raspberry Pi over and over again for both inspiration and reference. Whether you're an electronics professional, an entrepreneurial maker, or just looking for more detailed information on the Raspberry Pi, this is exactly the book for you.